The Needs Analysis in Developing An English E-Book of Berau’s and Paser’s Folklores by Using Flipbook Maker Application for Extensive Reading Classes of University Students: Lecturers’ Voice - Yuli Puji Astutik; Rudi Hartono; Mursid Saleh (Universitas Negeri Semarang, 2022)
As a part of Research & Development, needs analysis cannot be separated from the overall process. This paper was aimed at analyzing the need in developing an English e-book of Berau’s and Paser’s folklore by using the Flipbook Maker application for Extensive Reading (ER) classes of university students based on the perspective of the lecturers. The researcher used a descriptive qualitative approach in investigating the needs to meet the research objective. She used a questionnaire to collect the data from 8 English lecturers in five universities in East Kalimantan. The research finding showed that almost all the lecturers understood that ER is a program that can improve students’ skills in every aspect of English. They implemented ER to make their students love reading. They suggested that the material of ER should be non-authentic material including culture or local wisdom. They thought that the material should be a combination of printed and displayed (e-book) material. All of the lecturers suggested that ER should be implemented at schools to support English teaching and learning, and teachers need to provide them with some interesting books or watch videos or movies with English subtitles.